1996
DOI: 10.1046/j.1365-2265.1996.626446.x
|View full text |Cite
|
Sign up to set email alerts
|

Hexarelin, a synthetic growth hormone releasing peptide, stimulates prolactin secretion in acromegalic but not in hyperprolactinaemic patients

Abstract: Our data show that the PRL releasing effect of hexarelin is preserved in acromegaly but lost in pathological hyperprolactinaemia. In contrast with acromegaly, the GH releasing effect of hexarelin is also blunted in hyperprolactinaemic patients. These data demonstrate that patients with pathological hyperprolactinaemia are partially refractory to the activity of hexarelin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 20 publications
1
14
1
Order By: Relevance
“…GHRPs release PRL from human pituitary (24) and the GHRP-induced PRL rise is preserved in acromegalic patients bearing a somatomammotrope adenoma but not in patients bearing a pure prolactinoma (25). The evidence that HEX-induced PRL release does not vary with age suggests that the PRL-releasing effect of GHRPs is not influenced by estrogen levels and dopaminergic tone, which play a well-known role in the age-related variations of both spontaneous and stimulated PRL secretion (28).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…GHRPs release PRL from human pituitary (24) and the GHRP-induced PRL rise is preserved in acromegalic patients bearing a somatomammotrope adenoma but not in patients bearing a pure prolactinoma (25). The evidence that HEX-induced PRL release does not vary with age suggests that the PRL-releasing effect of GHRPs is not influenced by estrogen levels and dopaminergic tone, which play a well-known role in the age-related variations of both spontaneous and stimulated PRL secretion (28).…”
Section: Discussionmentioning
confidence: 80%
“…Concerning the PRL-releasing activity of GHRPs, very little is known about the mechanism underlying this effect, though a direct effect at the pituitary level has been hypothesized (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…However, GHS administration to patients with prolactinomas does not stimulate further PRL release, and the GH response is blunted [78]. We also showed that ghrelin stimulates proliferation of GH3 cells, a somatomammotroph tumour cell line, via activation of the MAPK pathway.…”
Section: Ghrelin In Prolactinomasmentioning
confidence: 79%
“…This is the first report on the effects of ghrelin in patients with acromegaly and it shows that chronic GH hypersecretion does not markedly influence the hormone responses per se. GHS receptor expression is very high in GH-producing adenomas (16) and hexarelin, a synthetic GHS, possesses GH-and PRL-releasing activity in acromegalic patients (17,18). The positive correlation between the extent of the ghrelin-elicited GH increase and the basal IGF-I concentrations in acromegalic patients suggests that GHSs are useful tools in assessing GH secretory capacity in both normal and pathological conditions, in agreement with previous findings in healthy subjects after hexarelin administration (19).…”
Section: Discussionmentioning
confidence: 99%